Amelia Bedelia - Parish, Peggy; Siebel, Fritz ([New York] HarperTrophy, 1992)
A literal-minded housekeeper causes a ruckus in the household when she attempts to make sense of some instructions.
Original ed. published 1963.
"Level 2. grade 1-3."
Keywords: Amelia-Bedelia (Fictitious character) -- Juvenile fiction; Humorous stories